Faktor Risiko Pasien Batu Ginjal Rawat Jalan RSUD Dr. Doris Sylvanus Palangkaraya - Yetti Wira Citerawati SY; Erma Nurjanah Widiastuti; Retno Ayu Hapsari (Poltekkes Kemenkes Pontianak, 2018)
Abstract: Risk Factors Of Outpatient With Kidney Stone In Dr. Doris Sylvanus Regional Public Hospital Of Palangkaraya . Kidney stones are crystalline structures in the urinary tract that have achieved sufficient size to cause symptoms (Alla, 2008). The most commonly formed kidney stones is calcium oxalate stones (80%). Based on data on the number of new cases in 2015 obtained on Medical Record Installation at Dr. Doris Sylvanus Regional Public Hospital of Palangka Raya was 1212 people during the period of January to December, thus the average patient was approximately 101 monthly. The research purpose was to understanding the relationship of intake (oxalate, protein, calcium, fluid), activity and level of knowledge with dietary compliance of kidney stone patients at Dr. Doris Sylvanus Regional Public Hospital of Palangka Raya. A cross sectional design was used in this research and subjects of the study were outpatients with kidney stones in Urology Medicine Polyclinic of Dr. Doris Sylvanus Regional Public Hospital of Palangka Raya. Chi Square test was conducted for bivariate analysis, furthemore, multiple logistic regression test was used for multivariate. The result of bivariate analysis showed that there was a significant relationship between fluid intake and activity with dietary compliance of kidney stone patients (p value = 0,05 and p value = 0,001), while there was no significant relationship in other variable such as oxalate intake , protein, calcium and level of knowledge. The results of multiple regression logistic test showed that the most influencing variable of dietary compliance of outpatients with kidney stones in Dr. Doris Sylvanus Regional Public Hospital of Palangka Raya is activity variable ( p value = 0,001).Abstrak: Faktor Risiko Pasien Batu Ginjal Rawat Jalan RSUD Dr. Doris Sylvanus Palangkaraya. Â Batu ginjal merupakan terbentuknya struktur kristal di saluran kemih yang telah mencapai ukuran cukup sehingga menimbulkan gejala (Alla, 2008). Batu ginjal yang paling sering terbentuk adalah batu kalsium oksalat (80%). Kasus baru pada tahun 2015 di RSUD Dr. Doris Sylvanus dari Januari hingga Desember sebanyak 1212 orang, sehingga rata-rata pasien perbulannya 101 orang. Tujuan penelitian untuk mengetahui hubungan asupan (oksalat, protein, kalsium,cairan), aktivitas dan pengetahuan dengan kepatuhan diet pasien batu ginjal rawat jalan Di RSUD Dr. Doris Sylvanus. Desain cross sectional dengan subjek penelitian pasien batu ginjal yang menjalani rawat jalan di Poli Urologi RSUD Dr. Doris Sylvanus. Analisis menggunakan uji Chi Square dan multiple logistic regression. Hasil menunjukkan terdapat hubungan yang bermakna antara asupan cairan dan aktivitas dengan kepatuhan diet pasien batu ginjal (p=0,05 dan p= 0,001). Sedangkan yang tidak berhubungan adalah asupan oksalat, protein, kalsium dan pengetahuan. Hasil analisis menggunakan multiple logistic regression menunjukkan bahwa variabel yang paling mempengaruhi kepatuhan diet adalah aktivitas (p=0,001).